Takayasu arteritis presenting as renovascular hypertension with hypertensive encephalopathy - Tanwar, Vikram Singh; Saini, Anjali; Singh, Anurag Ambroz; Tank, Rakesh (Journal of Advances in Internal Medicine, 2017)
Takayasu arteritis is a large vessel vasculitis that has variable presentation. It is suspected when there are pulse and BP discrepancies between upper limbs or absent pulses. We here presenting a case of takayasu arteritis that remained undiagnosed till 40 years and at first time manifested with hypertensive encephalopathy and managed well with medical therapy.Journal of Advances in Internal Medicine 2017;06(02):35-37.